THE POETİCS OF CİVİLİZATİON: FROM CONQUEST TO COLLAPSE İN ANDALUSİAN ARABİC POETRY - Üstün, Mahmut; Şen, Ahmet; Çiçek, Yeliz; Dağli, Erkan (Veredas do Direito, 2026)
This study examines Andalusian Arabic poetry not merely within the framework of literary genres or chronological periods, but as an aesthetic locus of memory reflecting the emergence, maturation, and dissolution of a civilization. The study explores the intricate relationship between poetry, political power, social structure, and cultural identity across the historical trajectory spanning from the initial conquest in 711 to the fall of Granada in 1492. The research demonstrates that while the classical poetic tradition centered in the East remained dominant during the periods of conquest and initial organization, geographical nuances, emotionality, and local elements progressively permeated the poetry. It is revealed that during the Caliphate and the Muluk al-Tawa’if (Taifa) periods, poetry reached its aesthetic zenith, evolving into a discourse that legitimized political power through panegyrics, descriptive verses, and nature poetry. Furthermore, the study emphasizes that uniquely Andalusian genres such as the Muwashshah served as the poetic expression of a multicultural and multilingual societal structure. In the Nasrid period, it is identified that poetry was primarily shaped around themes of sorrow, loss, and melancholy; specifically, in the works of Abu al-Baqa al-Rundi and his successors, the transformation of Al-Andalus into a 'civilization of memory' is reflected as a form of aesthetic resistance. By making the interaction between political history and aesthetic consciousness visible, the study aims to demonstrate how a civilization is constructed and dissolved through a poetic memory.